Comparison of Eddy Rumpoko's Leadership for Business Actors and Activists (Study in City Communities in 2023) - Prasetya, Bayu Agung (Universitas Medan Area, 2024)
The purpose of this research is to determine the comparison of Eddy Rumpoko's leadership towards the people of Batu City. This research uses empirical research methods with a qualitative descriptive approach. Primary data was collected through field data sources, while secondary data was obtained from books and statutory regulations. This research will use data collection techniques through observation and in-depth interviews. The research results show that business people consider that Eddy Rumpoko contributed to increasing business income during and after his reign. This is proven by the increase in residents' finances up to 3x and the massive growth in hotel rooms from around 6000 rooms to 8000 hotel rooms in Batu City. Business people gain financial prosperity with Eddy Rumpoko's leadership. However, Walhi activists consider that Eddy Rumpoko is accused of a corruption case which makes him a bad Regional Head of Batu City with around 46.8 billion in his leadership. Apart from the issue of corruption, there are environmental conflicts suffered by the people of Batu City, namely the conflict between The Rajya Hotel and Jatim Park 3 Batu City.